THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR)REPORTING, CORPORATE LEVERAGE, AND COMPANY AGE ON FINANCIAL PERFORMANCE OF BANKING IN INDONESIA(STUDY ON BANKS LISTED ON IDX IN 2018-2019) - Maulanda, Fadrian Dwiki (Jurnal Ilmiah Mahasiswa FEB, 2020)
The purpose of this research is to discover the influence of Corporate SocialResponsibility (CSR) Reporting, Corporate Leverage, and CompanyAge on financialperformance of banking in Indonesia on banks listed on IDX in 2018-2019. Thesampling was conducted through the non-probability technique, and purposivesampling, acquiring. 60 Banks in Indonesia on banks listed onIDXduring researchperiods. This research used content analysis calculation techniques for dataprocessing and effect testing with multiple regression tests. The results show that CSRReporting and Corporate Leverage have negative influence the financial performance,while Company Age have no significant influence the financial performance.Keywords: CSR, Corporate Leverage, Company Age, Financial Performance,Bank